Transcriptome Analysis of Sclerotium rolfsii: Unraveling Impact of Glycolytic Pathway on Substrate Utilization and Microbial Polysaccharide Production - Jia Song; Junfeng Li; Chenrui Zhen; Juan Du; Rui Zhao; Bingqian Fan; Jiayi Hou; Bingning Gao; Yu Zheng; Linna Tu; Min Wang (Fermentation)
Scleroglucan is the extracellular polysaccharide (EPS) produced by Sclerotium rolfsii (S. rolfsii). The low EPS titer and limited substrate utilization of S. rolfsii present significant challenges in the fermentation process, restricting industrial applications of scleroglucan. In this study, we performed a transcriptomic analysis on the mycelium of S. rolfsii fermented with different carbon sources. The key genes involved in polysaccharide biosynthesis (6-phosphofructokinase 1 (PFK1), pyruvate decarboxylase (PDC), aldehyde dehydrogenase (NAD (P)+) (ALDH3), and acetyl-CoA synthase (ACS)) were identified and their roles in the process were investigated. The supplementation of specific precursors—fructose-6-phosphate, pyruvate, aldehydes, and acetate—was shown to enhance both the polysaccharide titer and substrate utilization. By adding precursors, the titer of SEPS produced in a 5 L fermentation tank reached 48.69 ± 3.8 g/L. Notably, the addition of these precursors increased the titer of EPS fermented with sucrose (SEPS) by 65.63% and substrate utilization by 119.3%, while the titer of EPS fermented with lactose (LEPS) rose by 80.29% and substrate utilization rose by 47.08%. These findings suggest that precursor supplementation can effectively improve polysaccharide production and substrate efficiency, thereby minimizing resource waste and environmental impact.